#TITLE_ALTERNATIVE# - RONALD JEFFERSON PURBA (NIM : 13104044); Pembimbing : Dr. Ir. I Made Astina
Electricity demand in Indonesia increase about 6-9% every year, while fossil fuel resources used in many electric generation rapidly decrease. Therefore, an effort is needed to increase electric power and efficiency of electric generation. In this research, Priok Power Plant was chosen since it is an electric generation with high technology and it has high thermal efficiency. Air temperature entering the compressor of a gas turbine in Priok Combined Cycle is around 30 oC. This condition is not the same with an operating standard according to ISO that is air temperature entering the compressor at 15 oC and relative humidity of 60%. Because of the compressor work is based on volumetric flow, this different condition makes the air mass flow rate decrease. Hence, air temperature entering the compressor need to be cooled so that air mass flow rate will be bigger. Increasing of the air mass flow rate will enhance power generation and increase efficiency of the gas turbine system. Futhermore, adding Organic Rankine Cycle (ORC) to utilize the HRSG exhausted gas heat. This waste heat will be changed to be ORC turbine work in order to generate power. The simulation results show that air temperature entering compressor decrease to 15 oC, the net power increases 21,64% and efficiency increases from 48,94% up to 51,87%. This result was reached in a condition that turbine inlet temperature (TIT) 1070 oC, HRSG exhaust gas temperature of 150 oC, ORC turbine inlet temperature of 140 oC, ORC turbine inlet pressure of 2,5 MPa, and working fluid in mechanical chiller system and ORC is R-600. Optimal condition is reached if pressure ratio in the gas turbine system at 16. Replacement of the existing gas turbine system is needed in the future, because pressure ratio in Priok Combined Cycle has is not optimal condition.